A chemical study of the essential oil of Clausena anisum-olens (Blanco) Merr. (Fam. Rutaceae) - De Jesus, Crisanta R.; Bernal-Santos, Rizalina (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1976)
A colorless, with a sweetish anise-like odor, essential oil was obtained from the stem and fruit of Clausena anisum-olens (Blanco) Merr. at an average yield of 0.52% and 1.37%, respectively. The fruit oil gave the following physicochemical constants: specific gravity (28°C), 0.9588; refractive index (27°C), 1.5288; specific rotation (27°C), 0.949; acid value, 1.275, and saponification value, 7.63. Due to the small amount of oil obtained from the stem, only refractive index (27°C), 1.5169 was determined. Thin layer chromatographic and ultraviolet spectrophotometric results show that the constituents of both stem oil and fruit oil are almost the sa
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman, 1976.
Keywords: Essences and essential oi; Clausena ani